2013
DOI: 10.1001/jamadermatol.2013.4114
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between theHLA-B*1502Allele and Carbamazepine-Induced Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis

Abstract: We found a strong relationship between the HLA-B*1502 allele and carbamazepine-induced SJS and TEN in Han-Chinese, Thai, and Malaysian populations. HLA-B*1502 screening in patients requiring carbamazepine therapy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(102 citation statements)
references
References 50 publications
(51 reference statements)
3
86
0
1
Order By: Relevance
“…The majority of known genetic knowledge is derived from Caucasian populations [18]. The relative frequency of alleles important for pharmacogenomics varies by population, meaning that certain drugs or drug groups will be less effective or even hazardous in some populations, e.g., the risk for toxic epidermal necrolysis with the antiepileptic drug carbamazepine in East Asians [24], and more effective and safer in other such as statin use in Iranians with a specific KIF6 variant [11].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of known genetic knowledge is derived from Caucasian populations [18]. The relative frequency of alleles important for pharmacogenomics varies by population, meaning that certain drugs or drug groups will be less effective or even hazardous in some populations, e.g., the risk for toxic epidermal necrolysis with the antiepileptic drug carbamazepine in East Asians [24], and more effective and safer in other such as statin use in Iranians with a specific KIF6 variant [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, the association only manifests in SE Asians (table 1) and not Africans, Caucasians, or East Asians (Japanese, Koreans) [15,16,17]. One meta-analysis combined the published case-control studies on different populations and confirmed the association in SE Asians, with an integrated OR of 79.84 (95% CI 28.45-224.06) [18]. The ethnic-specific nature of the association between CBZ-SJS/TEN and HLA-B * 1502 relates to the difference of allele frequency in different populations.…”
Section: Pharmacogenomics Study Of Drug-induced Sjs/ten: Association mentioning
confidence: 96%
“…Stevens-Johnson syndrome is also reported in India secically in HIV patients. Phenytoin-induced risk is also identified in Japanese and Euporeans who carries HLA-A301 allele [27][28][29][30][31][32][33][34][35][36].…”
Section: Implications: Pathophysiologymentioning
confidence: 99%